2000
DOI: 10.1016/s0167-4889(00)00050-1
|View full text |Cite
|
Sign up to set email alerts
|

High glucose attenuates insulin-induced mitogen-activated protein kinase phosphatase-1 (MKP-1) expression in vascular smooth muscle cells

Abstract: The mechanisms for the effect of hyperglycemia on insulin-induced mitogenesis were investigated using rat vascular smooth muscle cells (VSMC). VSMC were preincubated in serum-free medium with low (5 mM) glucose (LG condition) or high (25 mM) glucose (HG condition), and examined for DNA synthesis using bromodeoxyuridine (BrdUrd) incorporation. Mitogen-activated protein kinase (MAPK) activity and MAPK phosphatase (MKP-1) protein expression were detected by Western blot analysis. Phosphatidylinositol 3-kinase (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Rat mesangial cells exposed to high glucose had decreased DUSP1 (3). In rat vascular smooth muscle cells, hyperglycemia inhibited insulin-induced DUSP1 and PI3K expression (37). Wortmannin, the PI3K inhibitor, blocked insulin- …”
Section: Discussionmentioning
confidence: 96%
“…Rat mesangial cells exposed to high glucose had decreased DUSP1 (3). In rat vascular smooth muscle cells, hyperglycemia inhibited insulin-induced DUSP1 and PI3K expression (37). Wortmannin, the PI3K inhibitor, blocked insulin- …”
Section: Discussionmentioning
confidence: 96%
“…For instance, insulin has been shown to increase the expression of mitogen-activated protein kinase phosphatase (MKP-1) in a PI3K-dependent manner (Desbois-Mouthon et al, 2000;Takehara et al, 2000), and this phosphatase negatively regulates IL-6 and TNF-␣ production in endotoxemic mice (Chi et al, 2006). Furthermore, a recent study showed that insulin and a glycogen synthase kinase 3␤ inhibitor had similar anti-inflammatory effects in a rat model of sepsis (Dugo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, sustained vasodilation would plausibly lead to elevated glucose availability and thus counterregulatory failure due to hypothalamic overestimation of plasma glucose. Furthermore, ATII induces the expression of GLUT-1 (17) and MKP-1 (18), which some data suggest can act as a switch during hypoglycemia to stimulate phosphatidylinositol 3-kinase-mediated glucose metabolism (19,20). Clearly, the induction of GLUT-1, whose induction by chronic hypoglycemia had been previously reported (21), would plausibly serve a neuroprotective role by increasing the transport of glucose into the brain and by doing so lead to counterregulatory failure, as previously proposed (22).…”
Section: Discussionmentioning
confidence: 99%